The relationship between safety climate and safety performance - Mohd Yusof, Hussain (2013)
This study evaluated on employee safety perception at a paper manufacturing company with emphasize on relationship between safety climate and safety performance among employees in a paper manufacturing company in Pahang. This study examined the relationship between safety climate and safety performance in order to understand safety perception that has been practiced in Pascorp Paper Industries Berhad. Safety is utmost issue, however employer and employees does not feel it as an important process of long goal safety. Understanding the concept of workers safety will enhance employer understanding the safety requirement of Pascorp Paper and adhere legal requirements. The study found that factors influencing the success of the safety system are safety climate and safety performance in reducing occupational incidents. Using SPSS 19 to measure the result of studies and test of hypothesis perceived safety climate to achieve the safety performance in organization. The study noticed that there is no significant relationship between gender age and year of service status. While significant relationship between workers position, education level and safety performance